2018
DOI: 10.1002/ecs2.2166
|View full text |Cite
|
Sign up to set email alerts
|

Breeding phenology and performance for four swallows over 57 years: relationships with temperature and precipitation

Abstract: Climate change can drive population declines for many species, often through changes to their food supply. These changes can involve a mis-timing between periods of high food demand and peak food availability, typically from advances in breeding phenology, and/or an overall reduction in food availability. Aerial insectivores, birds that feed on insects caught in flight, are experiencing steep population declines possibly because of shifts in the timing and/or abundance of aerial insects. We determined whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 68 publications
2
37
1
1
Order By: Relevance
“…This contrasts with the results of other studies that have found a seasonal temperature to effect breeding phenology (Vedder 2012;Whitehouse et al 2013). Precipitation levels are also thought to affect the phenology and fitness of insectivorous birds (McKeller et al 2013;Imlay et al 2018). Great tits (Parus major) synchronize their breeding with the abundance of caterpillars to maximize food for their offspring (Visser et al 2006).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…This contrasts with the results of other studies that have found a seasonal temperature to effect breeding phenology (Vedder 2012;Whitehouse et al 2013). Precipitation levels are also thought to affect the phenology and fitness of insectivorous birds (McKeller et al 2013;Imlay et al 2018). Great tits (Parus major) synchronize their breeding with the abundance of caterpillars to maximize food for their offspring (Visser et al 2006).…”
Section: Discussionmentioning
confidence: 83%
“…Spring conditions could directly affect the timing of nesting, hatch date, and clutch size, but conditions prior to the breeding season may affect other factors such as food abundance and affect reproductive traits (Nussey et al 2005). Moisture availability, measured as PDSI, may have stronger effects on populations than temperature alone due to ecological interactions such as insect abundance (Fei et al 2017;Imlay et al 2018).…”
Section: Climate Datamentioning
confidence: 99%
“…Kent Island has a shorter breeding period than more southerly sites, so the population may also be limited in its ability to compensate for stochastic weather events (e.g., by renesting). Further, a shorter breeding window could make it more difficult for Kent Island Tree Swallows to shift the timing of breeding in response to long-term climate trends, which may exacerbate phenological mismatches with the availability of insects (Dunn and Winkler 1999, Dunn et al 2011, Imlay et al 2018.…”
Section: Discussionmentioning
confidence: 99%
“…Populations of many aerial insectivores, including Tree Swallows (Tachycineta bicolor), have been declining in northeastern North America since at least the 1980s . The ecological and demographic mechanisms of ongoing declines are unclear but appear to be species-and region-specific (Nebel et al 2010, Smith et al 2015, Michel et al 2016, Imlay et al 2018. At broad scales, climate change may create a phenological mismatch between breeding and food availability, requiring Tree Swallows to adjust their breeding strategies or suffer population declines (Dunn and Winkler 1999, but see Dunn et al 2011, Imlay et al 2018.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation